Hubungan Lamanya Durasi Screentime Pada Usia 5 Tahun Terhadap Perkembangan Anak - Saputri, Eka Lusiani; Supriadi, Supriadi; Wahyuni, Rahmawati (Bunda Edu-Midwifery Journal (BEMJ), 2023)
This child development disorder can be influenced by the lifestyle of children who are not active. One form of inactive behavior is the use of screen time. A preliminary study at the Lok Bahu Health Center obtained data on the number of children aged 3-5 years from January to December 2022 totaling 275 children. Children aged 3-5 years who experienced developmental disorders included 19 speech-language disorders, 2 mental-emotional disorders, 4 motoric disorders, 9 independent socialization disorders and 3 other disorders. The aim is to determine the relationship between screentime duration at 5 years of age to childrens’s development. This type of research is analytic observation with a cross sectional design. The population is mothers who have children aged 5 years in the working area of the Lok Bahu Health Center in September-December 2022 as many as 68 people. The sampling technique is total sampling, so the sample is 68 people. Data analysis used the chi-square test. The duration of screen time at the age of 5 years was mostly from 39 people (57.4%) of High Screen Time respondents, while Low Screen Time was 29 people (42.6%). Most of the respondents according to child development were 43 people (63.2%), while doubtful were 25 people (36.8%). There is a relationship between the duration of screen time at the age of 5 years and children's development (p value : 0.000 less than α : 0.05). There is a relationship between screentime duration at 5 years of age to childrens’s development.